THE EFFECT OF ADDITION THE DIFFERENT CONCENTRATION OF TAPIOCA FLOUR ON CONSUMER ACCEPTANCE OF SURIMI CATFISH (Clarias gariepinus) FISHBALL - Indra, Renol Wisma; Sari, N Ira; ', Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aimed to determine the effect of addition the different concentration of tapioca flour on consumer acceptance of surimi catfish (Clarias gariepinus) fishball. The methode for this research was experimental methode with completely randomized designed non factorial with 4 treatments: B0 (without addition tapioca flour), B1 (15% of tapioca flour), B2 (20% of tapioca flour), and B3 (25% of tapioca flour). The parameter test was organoleptic and proxsimat analysis. The results showed that the addition 75 g (15% of tapioca flour) on fishball was the best treatment and most preferable by consumer acceptance, where as the fishballs have the criterias: appearance (good and nice, grayish white in colour); texture (chewy, compact and elastis); aroma (typical fishball and slightly fishy smell); and flavor (fish flavor and seasoning tested); with moisture content 68.84%, protein content 14.09% and fat content 0.58%.Keyword: Catfish, consumer acceptance, fishball, surimi.